2015
DOI: 10.7717/peerj-cs.30
|View full text |Cite
|
Sign up to set email alerts
|

The interplay of physical and social wellbeing in older adults: investigating the relationship between physical training and social interactions with virtual social environments

Abstract: Background. Regular physical activity can substantially improve the physical wellbeing of older adults, preventing several chronic diseases and increasing cognitive performance and mood. However, research has shown that older adults are the most sedentary segment of society, spending much of their time seated or inactive. A variety of barriers make it difficult for older adults to maintain an active lifestyle, including logistical difficulties in going to a gym (for some adults, leaving home can be challenging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 45 publications
4
19
0
Order By: Relevance
“…The bulletin board was also used, although visits were more related to a lurking behavior rather than actual contributions. We attribute this to automatic sharing of the participant’s performance (as a 3-star rating based on completeness) on the bulletin board ( social learning persuasion strategy [12]). The locker room comprises also an important percentage but it is mostly because of the fact that it preceded the classroom in the navigation.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The bulletin board was also used, although visits were more related to a lurking behavior rather than actual contributions. We attribute this to automatic sharing of the participant’s performance (as a 3-star rating based on completeness) on the bulletin board ( social learning persuasion strategy [12]). The locker room comprises also an important percentage but it is mostly because of the fact that it preceded the classroom in the navigation.…”
Section: Resultsmentioning
confidence: 99%
“…Both pilot studies were follow-ups to a previous pilot performed in Trento, Italy, and so they follow the same study design [12]. An overview of the study flow in consolidated standards of reporting trials–compliant format is shown in Figures 2 and 3.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations